Distribution of macroinvertebrates on intertidal rocky shores in Gorgona Island, Colombia (Tropical Eastern Pacific) - Londoño-Cruz, Edgardo (2014)
Organisms found on rocky shores must endure harsh environmental conditions during tidal changes but scientific studies on tropical rocky shores are scarce, particularly in Colombian shores. Here we describe the spatial distribution of macroinvertebrates associated to the intertidal rocky ecosystems of Gorgona Island, Colombia (Tropical Eastern Pacific). Sampling was carried out in four localities around the Island: La Ventana and La Camaronera (sampled during October 2010) and La Mancora and El Muelle (sampled during March 2011). Two methodologies were used: rapid ecological assessments for qualitative data and quadrats for quantitative data. The richness, abundance, diversity (Shannon-Wiener H’), and evenness (Pielou J’) of macroinvertebrates were determined for and compared between, using one way ANOVA, each locality and the three intertidal zones of La Ventana (see methods). One hundred twenty-one species of macroinvertebrates were found during the sampling period. In all localities, Mollusca was the richest and most abundant taxon (46% of the species and 59% of the individuals), followed by Crustacea (32% of the species and 33% of the individuals). The other groups accounted for the remaining 22% of the richness and 8% of the abundance. Several studies have demonstrated that mollusks and crustaceans are the richest and most abundant taxa in marine benthic communities. Most of the abundant species found were herbivores. The species composition varied among zones. The results of dominant species for each zone are consistent with the ones observed in other tropical rocky intertidal shores. All response variables showed a decreasing pattern from the low to the high intertidal (in La Ventana). Post-hoc results indicated that the high intertidal, the zone with the harshest environmental conditions, had significantly lower values than the other two zones for all response variables. Comparisons between the low intertidal zones of the different localities in Gorgona Island showed higher values in all response variables for localities with intertidal pools. The most topographically homogeneous localities showed the lowest richness, abundance, and diversity. Both, tide pools and substrate heterogeneity and/or micro-topography are known to offer refuge against extreme physical conditions to the intertidal dwelling organisms. Results suggest that environmental stress, heterogeneity, and stability are important factors affecting the spatial distribution of macroinvertebrate species on intertidal rocky shores of Gorgona Island. Rev. Biol. Trop. 62 (Suppl. 1): 189-198. Epub 2014 February 01.